Digitalizing and Protecting Archaeological Sites in The Kurdistan Region - Abdullah Khurshid Qader; Muhammad Hamakharib Muhammad (QALAAI ZANIST JOURNAL, 2022)
By mapping and digitalizing the archaeological sites, it is an important task in the process of protecting the heritage and archaeological sites. Digital protection of archaeological sites focuses on finding, developing and protecting archaeological sites. In other words, the digitalization of heritage and archaeology is the process of digitalizing the transmitted archaeological sites and not being moved using modern science of remote sensing in parallel with computer technology to obtain a three-dimensional digital archive to protect and renovate the archaeological sites in the event of their destruction. Having a digital archive of the foundation for the preservation of archaeological sites and heritage and the possibility of destruction of the archaeological sites will revive history. “The development of informational technology, such as artificial intelligence, virtual reality, multimedia, broadband network, and databases, has provided effective tools for heritage protection” (Zhou. et al, 2012 p.1). How these technologies are used to protect the history of archaeological sites digitally is now another task for modern archaeologists and scientists to protect the archaeological sites digitally in 3D models. In this regard, we focus on digitalizing the archaeological sites and electronically reviewing them in order to create a local database to create a photographic archive of archaeological and cultural sites.